'War Cry' or War Atrocity? A Note on Sinuhe B 140. Issue 1 (June 2018) - Morschauser, Scott
Virtually all translators render wd.n=i išnn ḥr i3t=f in Sinuhe B 140 as 'I raised a/my war/victory cry ( išnn ) over the back' of the nḫtw of Retenu. The author argues instead that išnn is an imperfective participial form derived from the verb šni, 'to conspire/curse', with the verbal noun being a term of execration applied to the rebellious nḫtw . Sinuhe's action of 'putting' ( wdi ) the condemned conspirator ( išnn ) 'on his back' points to the victor's display of his disgraced opponent's corpse.